6a + 2b + b - 4a= c + 5b + 7a - 2b - 2a=
7m + n - 2m - 4m + 3n

6c + a + b - 2c + a=
6a + 3b - 2a - 3b=
3a + b + 2a + c - b=

JahKhalib228 JahKhalib228    1   10.09.2020 18:24    0

Ответы
nik667755mm nik667755mm  15.10.2020 19:58

a) а+(4b+c)-а+4b+c б) а-(3b-2с)+a-зь+2с в) 2-(а-5)-2-а+5-7-а г) 2а-(b+3а)-2а-b-За%3D-а -b д) -(4а-2b)+(а-Зb)%3 -4а+2b+а-Зb%3D -За-b e) (5а-b)-(b-2а)-5а-b-b+2a-7a-2b ж) 7а-(2а-5b)+5b-7a-2a+5b-5a+5b%3D 3)2(5b-1)+3-10ь-2+3-10b+1 и) 4(Зb+2)-2(2b-3)-12b+8-4b+6-8b+14 к) 2а-(За-(4а-5))-2а-(3а-4а+5)-2а-За+4а-5 3За-5

ПОКАЗАТЬ ОТВЕТЫ
русскийязык150 русскийязык150  15.10.2020 19:58

Пошаговое объяснение:


6a + 2b + b - 4a= c + 5b + 7a - 2b - 2a= 7m + n - 2m - 4m + 3n 6c + a + b - 2c + a= 6a + 3b - 2a - 3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика